2011
DOI: 10.1002/bdrb.20329
|View full text |Cite
|
Sign up to set email alerts
|

Embryo developmental disruption during organogenesis produced by CF‐1 murine periconceptional alcohol consumption

Abstract: The aim was to study the control females (CF)-1 mouse embryo differentiation, growth, morphology on embryonic E- and N-cadherin expression at midgestation after periconceptional moderate alcohol ingestion. Adult female mice were exposed to 10% ethanol in drinking water for 17 days previous to and up to day 10 of gestation (ethanol-exposed females, EF) and were compared with nonexposed CF. EF presented reduced quantities of E10 to E10.5 embryos, greater percentage of embryos at stages less than E7.5, reduced im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 79 publications
(76 reference statements)
3
33
0
Order By: Relevance
“…This was later replicated with similar results in a mouse in vivo study (Cebral et al, 2000). When extending these experiments further, the research group showed that EtOH-exposed female mice had fewer embryos on E10, reduced implantation site numbers, increased resorption, delayed embryonic development and abnormal neural tube closure (Coll et al, 2011). In this study however, the PC period was defined as 17 days prior to conception until E10 (Coll et al, 2011), which is after embryonic implantation in mice.…”
Section: Periconceptional Alcohol Consumptionsupporting
confidence: 57%
See 1 more Smart Citation
“…This was later replicated with similar results in a mouse in vivo study (Cebral et al, 2000). When extending these experiments further, the research group showed that EtOH-exposed female mice had fewer embryos on E10, reduced implantation site numbers, increased resorption, delayed embryonic development and abnormal neural tube closure (Coll et al, 2011). In this study however, the PC period was defined as 17 days prior to conception until E10 (Coll et al, 2011), which is after embryonic implantation in mice.…”
Section: Periconceptional Alcohol Consumptionsupporting
confidence: 57%
“…When extending these experiments further, the research group showed that EtOH-exposed female mice had fewer embryos on E10, reduced implantation site numbers, increased resorption, delayed embryonic development and abnormal neural tube closure (Coll et al, 2011). In this study however, the PC period was defined as 17 days prior to conception until E10 (Coll et al, 2011), which is after embryonic implantation in mice.Collectively, these studies confirm that the early embryo is affected by EtOH, yet no one has investigated the long term consequences of PC alcohol. …”
mentioning
confidence: 92%
“…The major morphological phenotypes observed in embryos from ethanol‐treated females were open or abnormally closed neural tube or mal‐rotated embryos. The percentage of abnormal E10 embryos significantly increased in the ethanol‐treated group compared to controls (control, 9.5%; ethanol‐treated, 36.0% of abnormal E10 embryos over the total number of implantation sites [ p < 0.001]) (Coll et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in different animals suggested that ethanol as well as acetaldehyde, the primary oxidative metabolite of ethanol produced in vivo during placental detoxification (Brocardo et al, ), can lead to altered fetal development and growth (Bosco & Diaz, ). We previously demonstrated that maternal perigestational 10% ethanol administration up to Day 10 of gestation produced neural tube closure defects, altered embryonic tissues, and led to deficient cell adhesion with up‐regulated cadherin expression (Coll et al, ), increased production of embryo Prostaglandin E (Cebral et al, ), and deregulated prostaglandin‐nitric oxide pathways in organogenic E10 embryos. The present study demonstrated, for the first time, that short‐term, moderate ethanol intake before pregnancy and continuing up to early organogenesis in embryos—which produced low blood‐alcohol levels in an outbred mouse model—induced moderate oxidative stress in organogenic, E10 embryos, leading to deleterious oxidative stress‐related cellular and molecular effects in different organs and tissues of the ethanol‐exposed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinically relevant perturbations include periconceptional alcohol exposure that resulted in changes in E-and N-cadherin expression and slowed development of embryos (Coll et al 2011). Periconceptional alcohol exposure has also been shown to impair placental development that may contribute to fetal growth restriction (Gardebjer et al 2014).…”
Section: Sheep Modelsmentioning
confidence: 99%